When clarity backfires: How and when concrete labels undermine consumer appeal for plant-based burgers - Larrañaga Muguerza, Arancha (My University, 2026)
As consumers are increasingly encouraged to reduce meat consumption for environmental and health reasons, plant-based meat alternatives have gained importance, although their widespread adoption remains uneven. Prior research has shown that abstract labels (e.g., meat-free burger) enhance consumer appeal more than concrete, ingredient-based labels (e.g., soy burger); however, little is known about the psychological mechanisms that drive this effect. This study investigates how and when label abstraction influences product attractiveness, perceived taste and willingness to purchase. A between-subjects experiment was conducted, demonstrating that concrete labels heighten meat affinity, which in turn diminishes product attractiveness, perceived taste, and willingness to purchase. Gender moderated the indirect effects, with robust evidence for the pea label. Additionally, suggestive evidence at the 90% confidence interval indicates that men exhibited stronger resistance to soya and plant-based labels. This research contributes to theory by revealing how meat affinity mediates consumer resistance and suggesting that abstract labeling can enhance the adoption of plant-based foods. It also offers actionable insights for marketers and policymakers, such as combining abstract labels in the front with detailed information on the back and designing gender-sensitive marketing campaigns. It argues against strict labeling bans, showing that abstract terms may mitigate identity-based resistance.
Artículos en revistas
Keywords: Instituto de Investigación Tecnológica (IIT) - Innovación docente y Analytics (GIIDA)